Los estilos de crianza familiar y la autonomía en niños de 3 años, de jardín público, Víctor Larco-2021 - Leonardo Luis, Milagritos Estefani (2022)
The present research work entitled "Family parenting styles and autonomy in 3-year-old children, from public kindergarten, Víctor Larco-2021", had the purpose of finding the correlation of said variables mentioned above. The research was descriptive-correlational, with a sample of 10 children from the flexible green classroom and 10 children from the flexible red classroom of I.E 224 "Indoamérica", made up of 11 women and 9 men. The results obtained at the end of the statistical study showed that 75% of children receive an authoritarian parenting style, of which 45% have autonomy in relation to themselves and 30% have autonomy in relation to others; unlike the children who receive a permissive parenting style in which 15% was obtained, where 10% have autonomy in relation to themselves and 5% have autonomy in relation to others and finally 10% of children receive a democratic parenting style, in which 5% have autonomy in relation to themselves and the other 5% have autonomy in relation to others, concluding that there is a significant relationship between family parenting styles and the development of autonomy in 3-year-old children.